Histoplasmosis of the central nervous system. Issue 7 (July 1992) - Tan, V; Wilkins, P; Badve, S; Coppen, M; Lucas, S; Hay, R; Schon, F
Abstract : Histoplasma capsulatum infection of the central nervous system is extremely rare in the United Kingdom partly because the organism is not endemic. However, because the organism can remain quiescent in the lungs or the adrenal glands for over 40 years before dissemination, it increasingly needs to be considered in unexplained neurological disease particularly in people who lived in endemic areas as children. In this paper a rapidly progressive fatal myelopathy in an English man brought up in India was shown at necropsy to be due to histoplasmosis. The neurological features of this infection are reviewed.